2020
DOI: 10.4049/immunohorizons.2000083
|View full text |Cite
|
Sign up to set email alerts
|

IL-37 Expression Is Downregulated in Lesional Psoriasis Skin

Abstract: IL-37 broadly suppresses inflammation in various disease models. However, studies of the regulation and role of IL-37 in psoriasis are limited and contradictive. Using transcriptome analysis, PCR, protein determination, and immunofluorescence, we demonstrated marked downregulation of IL-37 in biopsies from human lesional psoriasis skin compared with paired samples of nonlesional skin. Immunofluorescence analysis showed that IL-37 was localized to stratum granulosum of the epidermis. TNF-a stimulation of normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…The most prominent reduction in IL-37 were observed in chronic AD lesional skin. Interestingly, it has previously been demonstrated that IL-37 expression is also reduced in psoriatic skin specimens (24). Owing to its anti-inflammatory properties, reduced levels of IL-37 might impact the inflammatory milieu of the skin microenvironment.…”
Section: Discussionmentioning
confidence: 98%
“…The most prominent reduction in IL-37 were observed in chronic AD lesional skin. Interestingly, it has previously been demonstrated that IL-37 expression is also reduced in psoriatic skin specimens (24). Owing to its anti-inflammatory properties, reduced levels of IL-37 might impact the inflammatory milieu of the skin microenvironment.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, injection of a human IL-37b expression vector reduced disease severity, cytokine production and skin mast cell density in a keratin 14 VEGF-A-transgenic mouse model of psoriasis (183). Finally, a single intradermal injection of recombinant mature human IL-37b tended to reduce epidermal thickness, although it did not decrease inflammatory cytokine expression in a model of Aldara (5% IMQ)-induced skin inflammation (236).…”
Section: Il-37 In Human Inflammatory Skin Diseasesmentioning
confidence: 94%
“…Several studies showed reduced IL37 mRNA expression in lesional psoriatic skin as compared to non-lesional and control skin (127,203,235,236). One study further indicated that successful treatment of psoriasis patients with the Janus kinase (JAK) inhibitor tofacitinib restored IL37 expression levels in the skin (237).…”
Section: Il-37 Expression Activity and Signalingmentioning
confidence: 99%
“…The therapeutic efficacy of anti-TNF-α/IL-23/IL-17A biologics for psoriasis suggests that the TNF-α/IL-23/IL-17A axis plays a central role in its pathogenesis ( 11 ). Although the precise role of IL-37 in the development of psoriasis remains unclear, intradermal injection of recombinant human IL-37 into a murine imiquimod-induced psoriasis model reportedly demonstrated a trend toward a protective effect ( 12 ). It has also been reported that IL-37 expression is markedly downregulated in biopsies from lesional psoriasis human skin compared with the level in paired samples of non-lesional skin ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the precise role of IL-37 in the development of psoriasis remains unclear, intradermal injection of recombinant human IL-37 into a murine imiquimod-induced psoriasis model reportedly demonstrated a trend toward a protective effect ( 12 ). It has also been reported that IL-37 expression is markedly downregulated in biopsies from lesional psoriasis human skin compared with the level in paired samples of non-lesional skin ( 12 , 13 ). These findings suggest that IL-37 may have potential to prevent the development of psoriasis, in addition to AD.…”
Section: Introductionmentioning
confidence: 99%